2000
DOI: 10.1001/archinte.160.4.517
|View full text |Cite
|
Sign up to set email alerts
|

Upper Gastrointestinal Tract Safety Profile of Alendronate

Abstract: In these older women, upper GI tract complaints, particularly dyspepsia and abdominal pain, were common, but alendronate treatment was not associated with an increased incidence of upper GI tract events, even in high-risk subgroups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
2
5

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(110 citation statements)
references
References 48 publications
7
96
2
5
Order By: Relevance
“…46,47 A trial including 6,459 postmenopausal women recorded the occurrence of severe adverse events (gastroduodenal perforations, ulcers, and bleeding events) and demonstrated a similar rate in the alendronate and placebo groups (1.6% and 1.9%, respectively). 48 That study included only female patients. In our study, the only significant adverse event occurred in one man out of 17 patients in the alendronate-treated group (5.8%).…”
Section: Discussionmentioning
confidence: 99%
“…46,47 A trial including 6,459 postmenopausal women recorded the occurrence of severe adverse events (gastroduodenal perforations, ulcers, and bleeding events) and demonstrated a similar rate in the alendronate and placebo groups (1.6% and 1.9%, respectively). 48 That study included only female patients. In our study, the only significant adverse event occurred in one man out of 17 patients in the alendronate-treated group (5.8%).…”
Section: Discussionmentioning
confidence: 99%
“…5 Cryer et al 6 also found that alendronate 70 mg once-weekly, used concomitantly with non-steroidal anti-inflammatory drugs, did not increase upper GI adverse events relative to placebo over three months. In a multi-center, 3-month, randomized, double-blind, placebo-controlled study by Greenspan et al, 7 the tolerability of once-weekly alendromate was evaluated in American patients with osteoporosis.…”
Section: Upper Gastrointestinal Tract Adverse Eventsmentioning
confidence: 96%
“…Bauer et al 5 investigated the upper GI tract safety of alendronate in the Fracture Intervention Trial (FIT). In this large, randomized, double-blind, placebocontrolled trial, American women taking alendronate 5mg/d or 10mg/d for osteoporosis were followed up for 3.8 years.…”
Section: A Introductionmentioning
confidence: 99%
“…Так, в крупном 3-летнем плацебоконтролируемом РКИ (n=6459) при изучении эффективности и безопасности алендроната в дозе 5-10 мг/сут количество язвенных поражений слизи-стой, кровотечений и перфораций в группе получавшей пре-парат оказалось даже чуть меньше, чем в группе плацебо -1,6 и 1,9% соответственно. Эзофагит был диагностирован у 0,7 и у 0,4% соответственно, различия незначимы [40]. Один из первых обзоров безопасности алендроната по данным на-циональной аптечной сети Великобритании был опублико-ван в 1996 г. На тот момент препарат принимали 475 тыс.…”
Section: бфunclassified